Penguatan Moderasi Beragama Melalui Pengembangan Digitalisasi Berbasis E-Learning Wasathiyah di Komunitas Mahasantri - Nurul Anam; Sayyidah Syaehotin (GUYUB: Journal of Community Engagement, 2025)
IAI Al-Qodiri Jember has a community of mahasantri with great potential to realize the role of PTKI as a laboratory for religious moderation in the digital era. However, this community faces challenges, such as the majority of the mahasantri not understanding the concept of moderation or wasathiyah, and they have never created or disseminated digital products oriented towards wasathiyah in the online world. The main objective of this community service is to implement and obtain results from the strategies carried out within the mahasantri community of the PAI program at IAI Al-Qodiri Jember. The method used in this service is the Community-Based Research (CBR) approach. The outcomes of this service are as follows: 1) the PAI program mahasantri community has developed awareness of facing issues of religious intolerance or extremism and has sparked the desire among the mahasantri to make changes through an educational-inclusive movement oriented toward the digitalization of religious moderation or wasathiyah; 2) the PAI program mahasantri community has been able to understand, comprehend, and formulate materials related to religious moderation or wasathiyah and wasathiyah materials from the PAI perspective (Qur’an-Hadith, Aqeedah-Akhlaq, Fiqh, or SKI); 3) the PAI program mahasantri community has been able to understand, comprehend, and formulate the significance of the digitalization of wasathiyah and can produce creativity in the form of results from the development of digitalization products based on wasathiyah e-learning; and 4) the PAI program mahasantri community has been able to carry out educational transformation actions by disseminating e-learning based wasathiyah digital products to educational institutions.